Rapid diagnosis in thyroid tumors by using touch cytology - Suzan Seno; Adnan Almarrawi; Mohannad Nasani; Safa Alhalabi (Archive of Biomedical Science and Engineering - Peertechz Publications, 2022)
The study aims to assess the role of imprint cytology in the diagnosis of thyroid nodules and compare it with paraffin Section in the diagnosis of thyroid lesions. It included 40 patients who visited Private Hospitals in Aleppo during the period from April to December 2021. The results indicated that there were 19 patients with thyroid cancer, representing 47.5%, of whom 14 were diagnosed with Papillary Carcinoma, with a percentage of 35%, and 5 cases with Follicular Carcinoma, with a percentage of 12.5%, while the remaining cases included 21 patients with Benign Adenomas at a rate of 52.5%, including 11 cases of Hashimoto's disease at a rate of 27.5% and 10 cases of Benign Follicular Tumors at a rate of 25%. These results were compared with Paraffin Sections and reached sensitivity, specificity, and accuracy in diagnosis for this technology, 94.73%, 95.23% and 95%, respectively, and the positive predictive value was 94.73%, while the negative predictive value was 95.23%. The results also indicated that this technology is fast in determining the Histologic Grading of Tumor Differentiation, but it does not determine the Histological Type. It also indicated that there was a significant association between gender and the incidence of thyroid tumors, while no significant statistical evidence was observed between age and the possibility of thyroid cancers.